ANALYSIS OF EXPENDITURE OF LABOR AND FINANCE IN TOPOGRAPHIC SURVEYING AT SCALE 1:25,000 IN MOUNTAIN REGIONS (ANALIZ ZATRAT TRUDA I DENEZHYKH SREDSTVPRI TOPOGRAFICHESKOI SEMKE V MASSHTABE 1:25,000 V GORNYKH RAIONAKH) - Kargashina,V. A.; Kirillova,V. S.; Naumova,A. I. (1968)
The article indicates the change in expenditures of labor and finance in topographic surveying of mountain regions at a scale of 1:25,000 depending upon the type of technology employed for the work. The calculations are completed by the Department of Economics of TsNIIGAiK (Central Scientific Research Institute of Geodesy, Aerial Surveying and Cartography) for four technological schemes - in 1956, 1960, 1961 and 1964 - on two technical projects, comprising survey sectors: I-with an area of 16,793 sq. km., and II-with an area of 16,574 sq. km. Each sector includes 224 trapezoids at a scale of 1:25,000. The regions of work are situated in an uncontoured, mountain-taiga location, where movement is possible only by pack animals. The elevation difference over the average surface of surveying sectors comprises plus or minus 350.800 meters. The work season lasts five months. (Author) Trans. of Geodeziya i Kartografiya (USSR) n12 p39-44 1965, by James Swisher.